Anaerobic co-digestion: Current status and perspectives. (June 2021) - Karki, Renisha; Chuenchart, Wachiranon; Surendra, K.C.; Shrestha, Shilva; Raskin, Lutgarde; Sung, Shihwu; Hashimoto, Andrew; Kumar Khanal, Samir
Graphical abstract: Highlights: Anaerobic co-digestion can overcome the drawbacks of mono-digestion. Usage of diverse feedstocks have different effects on co-digestion stability. Feedstock characterization is crucial for process efficiency. In-depth microbial analyses need to be conducted. Kinetic models for co-digestion need to be improved. Abstract: Anaerobic digestion is a long-established technology for the valorization of diverse organic wastes with concomitant generation of valuable resources. However, mono-digestion (i.e., anaerobic digestion using one feedstock) suffers from challenges associated with feedstock characteristics. Co-digestion using multiple feedstocks provides the potential to overcome these limitations. Significant research and development efforts have highlighted several inherent merits of co-digestion, including enhanced digestibility due to synergistic effects of co-substrates, better process stability, and higher nutrient value of the produced co-digestate. However, studies focused on the underlying effects of diverse co-feedstocks on digester performance and stability have not been synthesized so far. This review fills this gap by highlighting the limitations of mono-digestion and critically examining the benefits of co-digestion. Furthermore, this review discusses synergistic effect of co-substrates, characterization of microbial communities, the prediction of biogas production via different kinetic models, and highlights future research directions for the development of a sustainable biorefinery.